2000
DOI: 10.1046/j.1365-2265.2000.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

The insulin hypoglycaemia and overnight metyrapone tests in the assessment of the hypothalamic–pituitary–adrenal axis following pituitary surgery

Abstract: The overnight metyrapone test identified more patients with possible ACTH deficiency than the insulin hypoglycaemia test. Further follow-up of these patients is required before a final judgement can be made as to whether more subtle but clinically relevant ACTH deficiency can be detected by the metyrapone test. Our clinical follow-up to date would not support this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 14 publications
0
40
1
1
Order By: Relevance
“…Although controversy exists regarding the optimal test and optimal time for conducting tests in the postoperative period, the ITT is considered to be the gold standard test and is used as reference in clinical trials (6,7,9,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Although controversy exists regarding the optimal test and optimal time for conducting tests in the postoperative period, the ITT is considered to be the gold standard test and is used as reference in clinical trials (6,7,9,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…14,16,21,50,62,63 However, there have been reports of postoperative relapse despite complete disappearance of the preoperative positive desmopressin response. 4,17,28,39 In a series of more than 100 patients with CD, Losa et al demonstrated that 50 of 87 patients had a complete disappearance of positive preoperative response to desmopressin following surgery, yet 4 of these patients experienced a relapse shortly after surgery. Furthermore, 18 of 37 patients with continued positive response to desmopressin postoperatively were ultimately deemed to be in remission via dexamethasone suppression testing.…”
Section: Desmopressin Stimulationmentioning
confidence: 99%
“…63 However, the specificity of this test has been questioned in the setting of several follow-up reports of patients with recurrent CD with a wide range of 11-deoxycortisol values. 4,17,28 Consequently, the use of the metyrapone stimulation test for predicting CD recurrence has been limited. 28 …”
Section: Metyrapone Stimulationmentioning
confidence: 99%
“…In all cases, GHD was documented before start of rhGh replacement according to the international guidelines and when stimulation tests were performed. Severe GHD was defined as a GH peak response to the insulin tolerance test (ITT) <3 μg/L (glucose nadir <2.2 mmol/L) or, in case of contraindications for ITT, by the peak response to combined growth hormone-releasing hormone/arginine stimulation (GHRH/Arg) with BMIadjusted GH cutoffs (21,22,23,24,25,26). Of all the patients, 41 were diagnosed as GHD by insulin tolerance test and 20 by GHRH+arginine.…”
Section: The Diagnosis and Treatment Protocol Of Adult Patients With Ghdmentioning
confidence: 99%